The relationship between surface drug distribution of Dox-loaded microbubbles and drug release/cavitation behaviors with ultrasound - Chia-Wei Lin; Ching-Hsiang Fan; Chih-Kuang Yeh (Ultrasonics Sonochemistry, 2024)
Ultrasound (US)-triggered microbubbles (MBs) drug delivery is a promising tool for noninvasive and localized therapy. Several studies have shown the potential of drug-loaded MBs to boost the delivery of therapeutic substances to target tissue effectively. Nevertheless, little is known about the surface payload distribution affecting the cavitation activity and drug release behavior of the drug-loaded MBs. In this study, we designed a common chemodrug (Doxorubicin, Dox)-loaded MB (Dox-MBs) and regulated the payload distribution as uniform or cluster onto the outer surface of MBs. The Dox distribution on the MB shells was assessed by confocal fluorescence microscopic imaging. The acoustic properties of the Dox-MBs with different Dox distributions were evaluated by their acoustic stability and cavitation activities. The payload release and the fragments from Dox-MBs in response to different US parameters were measured and visualized by column chromatography and cryo-electron microscopy, respectively. By amalgamating these methodologies, we found that stable cavitation was sufficient for triggering uniform-loaded MBs to release their payload, but stable cavitation and inertial cavitation were required for cluster-loaded MBs. The released substances included free Dox and Dox-containing micelle/liposome; their portions depended on the payload distribution, acoustic pressure, cycle number, and sonication duration. Furthermore, we also revealed that the Dox-containing micelle/liposome in cluster-loaded MBs had the potential for multiple drug releases upon US sonication. This study compared uniform-loaded MBs and cluster-loaded MBs to enhance our comprehension of drug-loaded MBs mediated drug delivery.